Eksplorasi kekayaan sastra Arab dalam dunia modern - Aisah, Aas Siti (Maliki Interdisciplinary Journal, 2024)
The richness of Arabic literature has a broad and varied heritage, including various literary works such as poetry, prose and religious texts that have made significant contributions to the development of global culture. Arabic literature not only shows the beauty of language and creativity, but also reflects rich cultural, historical and philosophical values. In the context of the modern world, the exploration of Arabic literature offers a deep understanding of complex cultural and historical identities. These literary works are not only a source of inspiration for contemporary writers and poets, but also become material for study in various disciplines such as comparative literature, religious studies, and the history of civilization. In particular, Arabic poetry is often considered the form of expression that best represents deep emotional and aesthetic intelligence. Arabic prose, on the other hand, explores diverse themes, ranging from historical narratives, philosophy, to moral stories that are relevant to contemporary issues. This research discusses the relevance and influence of Arabic literature in the context of globalization and modernization, as well as how these literary works remain relevant and inspiring in facing the challenges of the modern era. This analysis provides a deeper understanding of the universal values ​​contained in Arabic literature, as well as their impact on global cultural development.